Late-life homelessness: experiences of disadvantage and unequal aging - Grenier, Amanda (McGill-Queen's University Press, 2021)
Section I: Context, frame, and methodology -- 1: Setting the context -- 2: The state of knowledge on late-life homelessness -- 3: A Critical perspective and ethnographic approach to late-life homelessness -- Section II: Project insights from four thematic angles -- 4: Age and late-life homelessness -- 5: The places of late-life homelessness : aging in "undesirable" locations -- 6: :Late-life homelessness as a reflection of disadvantage over time -- 7: Late-life homelessness as social exclusion and abandonment -- Section III: Direction for change -- 8: The need to prevent homelessness across the life course and into late life -- 9: The moral imperative: political and just responses to late-life homelessness.